Penerapan Mekanisme Pajak Penghasilan Final Umkm Berdasarkan Pasal 2 Sampai Dengan Pasal 7 Peraturan Pemerintah Nomor 23 Tahun 2018 Pada Perseroan Perorangan di Kabupaten Sarolangun Provinsi Jambi - Meylani, Sabrina (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study aims to examine the implementation of the Final Income Tax (Pajak Penghasilan Final) mechanism for MSMEs in Individual Corporations in Sarolangun Regency, Jambi Province. The method used is a qualitative approach with a field research type. Data were collected through documentation, observation, and in-depth interviews with employees of the Regional Revenue and Financial Management Office of Sarolangun Regency as well as the owners of Individual Corporations. Data analysis was conducted qualitatively through stages of data reduction, data presentation, and drawing conclusions. The results of this study indicate that the implementation of the Final Income Tax mechanism for MSMEs in Individual Corporations in Sarolangun has not fully complied with the provisions of Government Regulation No. 23 of 2018, particularly in terms of tariff application, understanding of the facility period, and compliance with tax payment and reporting obligations, which are influenced by the taxpayers’ level of understanding and the effectiveness of tax socialization.